Hydrothermal Preparation and White-Light-Controlled Resistive Switching Behavior of BaWO4 Nanospheres - Sun, Bai; Liu, Yonghong; Zhao, Wenxi; Wu, Jinggao; Chen, Peng (Nano-Micro Letters, 2014)
In this work, BaWO4 nanospheres were successfully prepared by hydrothermal process. The bipolar resistive switching behavior of Ag/BaWO4/FTO device is observed. Moreover, this resistive switching behavior can be modulated by white light. The device can maintain superior stability in the dark and under white-light illumination. This study is useful for developing the light-controlled nonvolatile memory devices.